Maritime Cybersecurity (Signals and Communication Technology, 2025)
This book highlights the importance of cybersecurity in the maritime domain, including the human and societal aspects of both cyber-crime and cyber-defense. The authors present mechanisms for early detection and prevention of cyber-attacks, as well as security protocols based on testbed nautical simulator experiments, machine learning algorithms and artificial intelligence applications. This collection of research articles addresses the ethical, societal and technical aspects of maritime cybersecurity and offers solutions to mitigate the threat of cyber-attacks. The book is designed to help both researchers and stakeholders across the maritime ecosystem, including shipping and port logistics. Research findings are presented in the following areas: human factors in maritime cyber security, cyber security awareness and skills of seafarers, vulnerabilities in electronic maritime navigation on manned and unmanned vessels, internal and external attack vectors on bridge and propulsion systems, cyber security threats and countermeasures in seaports. The book serves as a handbook for those professionally involved in or interested in cybersecurity of IT and OT systems. This book is open access, which means that you have free and unlimited access.